Relevance of community participation and concerned stakeholders in conservation management of Kainji lake national park, Nigeria (2021)
This study was to assess the participatory role of communities in the achievement of the National conservation goals at the Kainji Lake National Park (KLNP) by the active involvement of local people in park planning, formation, executing and implementing management strategies of renewable resources and its environment. Data were collected from the park annual reports, park management plan, research and information units and environ-consult reports. The Global Environmental Facility (GEF) through the Local Economic Empowerment Programme (LEEMP) provides a non-refundable grant while the World Bank with the assistance of the Internal Development Association (IDA) provides a refundable credit facility for local communities. These financial supports were aimed at providing alternative means of livelihood for the rural people in the community and to alleviate the poverty. The first stage considered ten (10) communities selected from the Borgu sector and the second stage also has ten (10) communities selected as well for their financial assistance. Constraints observed in the implementation of the programme includes lack of project vehicle, computer system and accessories, frequent changes in programme design and directives, lack of confidence in project administration, remoteness of the communities and lateness in release of the micro-projects fund. Successful implementation of the programme requires sound management and supervision of the project time frame. There is need for more in the future and should be based on revegetation mainly (afforestation) and not deforestation in the conservation environment.